2013
DOI: 10.1038/ncomms2616
|View full text |Cite
|
Sign up to set email alerts
|

Three-photon bosonic coalescence in an integrated tritter

Abstract: The main features of quantum mechanics reside in interference deriving from the superposition of different quantum states. While current quantum optical technology enables two-photon interference both in bulk and integrated systems, simultaneous interference of more than two particles, leading to richer quantum phenomena, is still a challenging task. Here we report the experimental observation of three-photon interference in an integrated three-port directional coupler realized by ultrafast laser writing. By e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
194
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(199 citation statements)
references
References 44 publications
5
194
0
Order By: Relevance
“…[18,35], formalized in Ref. [45] and taken further in this article overcomes the issues enumerated in Section II B: Since our central Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,35], formalized in Ref. [45] and taken further in this article overcomes the issues enumerated in Section II B: Since our central Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The computation of event probabilities in Ref. [35] was implicitly based on this approach, and a similar projection operator is also used in Ref. [48].…”
Section: Tensor-permanent Approach a Event Probability As Expecmentioning
confidence: 99%
See 1 more Smart Citation
“…In [13], one first experimental realization of a quantum walk implementing the qFFT has been reported as an effective platform for validating genuine quantum interference with many-photon states. The implementation of the qFFT interferometer has been realized on a photonic integrated platform by exploiting the 3-D capabilities of femtosecond laser writing technology [17,18], which enables the fabrication of quantum walks arranged in three-dimensional scalable architectures with arbitrary layouts [20][21][22][23]. Indeed, the integration of all beamsplitters and phase shifters into a monolithic structure leads to a fundamental increase in the stability and scalability of the whole apparatus.…”
Section: Experimental Realization Of a Fast Qftmentioning
confidence: 99%
“…The simplest case is the Hong-Ou-Mandel (HOM) effect when two particles impinge on distinct ports of a balanced beam splitter: quantum interference suppresses the coincident output (one particle per each output) in the case of bosons and the single-port output (both particles in either output) in case of fermions. In the multi-particle case, a sort of generalised HOM effect occurs for symmetric multiport beam splitters [5][6][7][8]. In particular, Tichy et al [7] showed that for a particular class of multiports, namely Bell or Fourier multiports, and input states with cyclic symmetry, a full suppression of most of the output combinations is observed; a * andrea.crespi@polimi.it simple analytical law gives a sufficient criterion for such suppression.…”
Section: Introductionmentioning
confidence: 99%